Eco-novel food and feed - Sousa, Isabel (2021)
This is a reprint of articles from the Special Issue published online in the open access journal Applied Sciences (ISSN 2076-3417) (available at: https://www.mdpi.com/journal/applsci/special issues/Eco-Novel Food Feed)